2017
DOI: 10.1038/s41467-017-01681-3
|View full text |Cite
|
Sign up to set email alerts
|

River-bed armouring as a granular segregation phenomenon

Abstract: River bed-load transport is a kind of dense granular flow, and such flows are known to segregate grains. While gravel-river beds typically have an “armoured” layer of coarse grains on the surface, which acts to protect finer particles underneath from erosion, the contribution of granular physics to river-bed armouring has not yet been investigated. Here we examine these connections in a laboratory river with bimodal sediment size, by tracking the motion of particles from the surface to deep inside the bed, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 62 publications
(111 reference statements)
3
73
1
Order By: Relevance
“…Recently, it has been found that such granular creep is very similar to kinetic sieving processes in dry granular flows [14]. The segregation phenomena we observed The last entry in the table was found by linear interpolation yield a similar outcome, but occur at much shorter time scales.…”
Section: Bidisperse Bedsupporting
confidence: 59%
“…Recently, it has been found that such granular creep is very similar to kinetic sieving processes in dry granular flows [14]. The segregation phenomena we observed The last entry in the table was found by linear interpolation yield a similar outcome, but occur at much shorter time scales.…”
Section: Bidisperse Bedsupporting
confidence: 59%
“…We found that sheetflow thickness increased with steeper bed slopes, unlike sheetflows at lower bed gradients, and particle velocities increased with bed shear velocity, similar to sheetflows on lower bed gradients . This is in contrast to discrete element modeling by Ferdowsi et al (2017), who found that creep motion in granular beds is independent of shear rate for Shields stresses up to five times the critical Shields stress, though they used bimodal sediment sizes and a horizontal flume bed slope. Understanding the conditions under which these highly-concentrated sheetflow layers occur is important, as they might be considered analogous to the body of a debris flow or occur where hyper-concentrated flood flows or debris floods have been observed (Wells, 1984;Sohn et al, 1999;Hungr et al, 2014), such as on alluvial fans (Stock, 2013).…”
Section: Mode Of Transport: Fluvial Versus Mass Flow Behaviorcontrasting
confidence: 40%
“…In the creeping regime, μ<μs, but flow events are triggered via the bedload transport regime at the top of the bed via spatial correlations in the force network. These creeping events, although slow and intermittent, can lead to segregation effects over long times ( 10–100 hr), where large particles are sorted to the top (Ferdowsi et al, ). Thus, creep and nonlocal rheology may play a crucial role in armoring of gravel‐bedded rivers, as opposed to size sorting in the transported layer.…”
Section: Yield and Flow Of Dense Granular Media In The Context Of Sedmentioning
confidence: 99%